Application of the arm-cranking 30-second Wingate Anaerobic Test (the WAnT) to assess power in amputee football players - Nowak, A. M.; Molik, B.; Kosmol, A.; Szczepaniak, M.; Marszalek, J. (Acta of Bioengineering and Biomechanics, 2021)
Purpose: The aim of this work was to determine anaerobic performance in male amputee football players considering types and levels of limb impairment, playing position, anthropometric parameters, and comparing the findings to reference values. Relationship between parameters in the laboratory anaerobic test and the handgrip test was checked. Methods: The 30-second Wingate Anaerobic Test (peak power, mean power, relative peak power, relative mean power, time to achieve peak power, fatigue index) on the arm-crank ergometer (LODE ANGIO), the FUTREX 6100 (Futrex, Gaithersburg, USA) and the handgrip test were used in amputee football players (n = 23). Anthropometric measurements were collected. Results: There were no differences in anaerobic results between players considering types and levels of limb impairment. Forwards had significantly higher relative mean and peak power ( p = 0.049, d = 0.82; p = 0.049, d = 0.81), and lower amputation-adjusted body mass index ( p = 0.001, d = 1.50) than defenders. For peak power, 19 out 23 achieved, and for relative peak power, 22 out 23 achieved results from "average" to "elite". Peak power strongly correlated to handgrip strength results. Conclusions: Amputee football requires a high level of power from players. Maintaining appropriate body composition is important for amputee football players to have better anaerobic performance during the game. The 30-second Wingate Anaerobic Test can be used to assess anaerobic performance in AF players. Sport-specific anaerobic performance laboratory tests and field-based tests using in indirect upper limbs` peak power monitoring would be beneficial for coaches.